P‐64: Mechanism Analysis of Defects on the Organic Film Process. Issue 1 (29th May 2019) - Zhang, Xiaoxiang; Ding, Xiangqian; Song, Yongzhi; Liu, Mingxuan; Jia, Yihe; Wu, Zumou; Li, Xiaolong; Han, Hao; Chen, Weitao
Abstract : Mechanism of pixel defect and dark‐line defect on the organic film process are studied in this paper, and improvement methods are also given. Reducing outgas by increasing the organic holes can avoid cracking in Org/PVX/ITO laminated structure. Increasing exposure dose can remove ITO residual in fan‐out zone, and mask design value that compensate the rise of DICD by increasing exposure dose are also given. Through the above improvement methods, pixel defect and dark‐line defect are solved and yield is enhanced from 50.2% to 99% which meets the requirement of mass production.